2008
DOI: 10.1093/protein/gzn055
|View full text |Cite
|
Sign up to set email alerts
|

Engineered humanized diabodies for microPET imaging of prostate stem cell antigen-expressing tumors

Abstract: We have previously demonstrated preclinical in vivo targeting of prostate stem cell antigen (PSCA) using a humanized anti-PSCA 2B3 monoclonal antibody (mAb). However, humanization resulted in 5-fold loss of apparent affinity relative to the parental mAb (1 nM). In this study, diabodies (scFv dimers of 55 kDa) were generated from 2B3 including variants with different linker lengths as well as back-mutations to original murine residues to improve affinity. Parental 2B3 (p2B3) and back-mutated 2B3 (bm2B3) diabodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
2
34
1
2
Order By: Relevance
“…We demonstrate that Ha1-4.117-based CARs presented superior surface expression in human T cells and conferred higher target recognition capabilities than a CAR based on bm2b3 (a variant of 2b3 with enhanced affinity) (Leyton et al, 2009), without compromising antigen specificity. This design is expected to prevent the development of an immune response directed to the remaining murine immunoglobulin regions present in 2b3-based CARs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We demonstrate that Ha1-4.117-based CARs presented superior surface expression in human T cells and conferred higher target recognition capabilities than a CAR based on bm2b3 (a variant of 2b3 with enhanced affinity) (Leyton et al, 2009), without compromising antigen specificity. This design is expected to prevent the development of an immune response directed to the remaining murine immunoglobulin regions present in 2b3-based CARs.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we generated an anti-PSCA CAR derived from humanized mouse antibody bm2b3 (Fig. 2a) (Leyton et al, 2008(Leyton et al, , 2009). These CAR sequences were inserted into retroviral vectors and used to transduce human PBL.…”
Section: Psca Mrna Expression In Tumors Pancreatic Cancer Cell Linesmentioning
confidence: 99%
“…In this study, we have used antibodies in SIP format (Borsi et al, 2002;Villa et al, 2008), as this format and similar mini-antibody formats have extensively been shown to offer distinctive advantages both for imaging applications (Leyton et al, 2009);von Lukowicz et al, 2007;Wei et al, 2008) and for radioimmunotherapy of cancer (Berndorff et al, 2005;Tijink et al, 2006;Kenanova et al, 2007;Sauer et al, 2009). Recent publications suggest that smaller high-affinity ligands (MW o 2000 Da) may enjoy a much more rapid tissue distribution compared with antibodies and antibody fragments (Low et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The scFv were all designed in the V L -V H orientation and the linker lengths were one, three, five and eight residues. Although linker lengths of ,12 residues will generally force dimerization of the scFv fragments, we have observed that linkers of eight residues can produce a mixture of monomers and dimers and that the ratio between the two species was concentration-dependent (Leyton et al, 2009). For this reason, we decided to engineer another anti-CD20 scFv fragment with the more commonly used linker length of five amino acids.…”
Section: Anti-cd20 Diabodies Discussionmentioning
confidence: 99%